(untitled) (Research, Society and Development, 2023)
Cancer comprises the rapid and disordered growth of atypical cells, composing a set of diseases, with the ability to invade tissues and organs from different parts of the body. In children and adolescents, aged between 0 and 19 years, cancer is usually embryonic in nature and by undifferentiated cells. The aim of the research is to identify the epidemiological panorama of the main types of childhood cancers in the northeast region of Brazil from 2012 to 2021. This is an observational and descriptive study, carried out from February to June 2022, using the TABNET database of the Ministry of Health (MH) in DATASUS. According to the SUS Hospital Information System, the northeast region of Brazil had a total of eighty-eight thousand, eight hundred and thirty-two hospitalizations for the main types of childhood cancers in the last ten years. In view of the results, it is clear that the state of Pernambuco has the highest number of hospitalizations with 31% of cases, followed by the state of Bahia (20%) and Maranhão (10%), respectively. The states of Ceará, Rio Grande do Norte and Piauí appear with 8% each, followed by Paraíba (7%), Alagoas (6%) and Sergipe (2%). It was found that in the Northeast region of Brazil in the last ten years the most prevalent type of cancer was leukemia regardless of age group and sex.